Modelling the seasonality of hotel nights in Denmark by county and nationality - Nils Karl Sorensen (European Regional Science Association (ERSA), 2001)
The paper examines foreigners demand for hotel nights in Denmark by nationality using monthly time series covering nearly 30 years. Inbound hotel demand is assumed to depend on economic variables like the foreign and Danish CPI and the exchange rate, as well as variables measuring the climate. It is investigated weather the climate last year has a significant influence on this year demand for hotels. Further, the relative importance between economic and climatic variables are considered. Univariate as well as multivatiate ECM models are examined, and special attention is devoted to an evaluation of the forecast performance of the various models. Over time people's preferences have changes, and this implication for modelling demand is taken into account. Key words: Tourism, seasonality, forecasting, multivatiate estimation, cointegration. Theme: Tourism and regional development, econometrics.
Keywords: 330